Green Synthesized Titanium Dioxide Nanoparticles from date seed for photocatalytic dye degradation - Hussain, Mohamed Abdelkalik; Al Sieadi, Wadhah Naji (Iraqi Journal of Science, 2025)
One of the most pressing challenges in the field of photocatalysis is the development of efficient photodegradation systems that utilize different ultraviolet light spectra and nanoparticles as photocatalysts to effectively remove pollutants from the environment. This study investigates the photodegradation efficiency of methylene blue dye under three different types of UV light sources using a new homemade instrument. The photodegradation activity of this system comprises various conditions, the first one is for MB dye only, the second one is when irradiation of MB dye with UV-A, UV-B, UV-C light sources with circulation, finally, the effect of adding 0.05 gm of green synthesis of TiO2NPs by using date seed powder in sol-gel method. Different percentages of MB dye removal were reported. The prepared catalysts were characterized using Ultraviolet-visible spectroscopy, Fourier transform infrared spectroscopy, Scanning electron microscope, Energy dispersive analysis, X-ray spectroscopy, and atomic force microscopy. The photodegradation performance under UV-C irradiation was the highest, showing 98% photodegradation of MB dye in 90 minutes. UV-B irradiation showed 86% photodegradation of MB dye in 90 minutes, while UV-A irradiation showed 36% photodegradation of MB dye in 90 minutes.